Foot care needs for children and young people with intellectual and developmental disabilities. (19th September 2019) - Morrison, Stewart C.; Barrett, Laura; Haines, David
Accessible Summary: We asked parents of children with intellectual and developmental disabilities to complete a survey to help us understand more about the foot problems their children have experienced. Parents told us that foot problems were common in their children, 75% of the parents raised this as a concern. Less than half of the parents felt confident with managing these problems. Buying shoes was considered difficult. The results from this survey tell us that foot problems in children and young people with intellectual and developmental disabilities are a concern. It is important to ensure that children have access to foot care services. Abstract: Background: Foot problems have been reported to be a very common health issue in adults with intellectual disabilities; foot problems in children and young people are, however, poorly understood. The aim of this study was to explore foot care needs of children and young people with intellectual and developmental disability. Methods: An exploratory, cross‐sectional online survey was undertaken across a four‐month period. A purposive snowball sampling approach was adopted. The survey tool was piloted before launch and comprised three sections. The first section elicited information relating to parent/caregiver status, diagnosis, secondary diagnoses and age of child/young person. The second domain explored foot care and sought to obtain information about foot problems, access to health services and existing knowledge about foot health. The third domain focussed on footwear. Ethical approval was granted from the host institution, and all participants provided electronic consent before completing the survey. Results: Data were collected from 49 parents/parental caregivers reporting on behalf of their children (mean age 7 years of age; SD 4.5 years of age). Parents reported foot problems to be very common (75%), and pes planus was the most frequent concern (51%). Twenty‐four parents reported difficulties with finding shoes (48%). A mismatch between foot shape and the shoe (30%) or complications with orthotic devices (14%) within the shoe were highlighted. Conclusion: The results demonstrated that the burden of foot problems in children and young people with intellectual and developmental disabilities is considerable. The findings highlight the importance of access to foot care services for these children.